KETERKAITAN SENI PERTUNJUKAN DENGAN MALE GAZE, OBJEKTIFIKASI WANITA, DAN KEKUASAAN PENONTON (STUDI KASUS: RHYTHM 0 KARYA MARINA ABRAMOVIĆ) - Sandra, Ni Putu Anindhita Ayesha (PT. Hasba Edukasi Mandiri, 2026)
This research explores the dynamics of power and gender objectification in performance art through an analysis of Marina Abramović’s work, Rhythm 0 (1974), which is a performance involving extreme audience participation that sparked global debate regarding ethical boundaries in art. Employing a qualitative approach, this study dissects the interaction between artist and audience through the lens of the male gaze, which is a visual modality that positions women as objects of masculine desire or control, as well as theories of power within Visual Culture. The analysis demonstrates that Abramović's instructions created a power shift, transforming the audience from observers into dominant actors who subjected her to exploitation and objectification. The findings of this research provide insight into human responses when granted absolute power, while simultaneously confirming the vulnerability of the female body to exploitation in public spaces. Furthermore, this study serves as a case study highlighting how patriarchal culture and supremacy over human vulnerability can manifest in simple situations, including simulations and art performances.